INORGANIC NITROGEN REMOVAL IN TROPICALLY COASTAL AQUACULTURE PONDS USING INTEGRATED BIOREMEDIATION - Hao, Do Manh; Anh, Dao Thi Tuyet; Nga, Hoang Thi Thanh; Dat, Nguyen Tien; Sinh, Le Xuan; Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2017)
Bioremediation technology has been emergently considered as an economic and environmental-friendly manner to treat inorganic nitrogen in tropically coastal aquaculture ponds. Two laboratory scale experiments were conducted to examine efficacy of nitrogen removal of some bioremediators. The results indicated that total ammonia nitrogen (TAN) and nitrite concentrations of treatments with inoculation of the nitrifying bacterial cultures were significantly lower than those of the treatments without inoculation just after three days and one day of experiment, respectively. TAN in treatments with inoculation was removed at 76.0% while that without inoculation was just removed at 53.7%. Nitrite in treatments without inoculation increased duration of first 20 experiment days while nitrite in treatments with inoculation decreased to 50% just after one day. For treatments with inoculation of denitrifying bacterial cultures, effect of nitrate removal was clear within one day after beginning of the experiment. The present of macroalgae Gracilaria sp. promoted TAN and nitrite removal after two to three days of the experiment. Moreover, the addition of CaCO3 could enhance TAN and nitrite removal in comparison to the control treatments.